Studies toward the total synthesis of (+)-neopeltolide using N-heterocyclic carbene-catalyzed oxo-acyloxylation/reductive oxa-Michael addition strategy - Reddi, Rambabu N.; Sudalai, Arumugam; Jo, Changbum (Bulletin of the Korean Chemical Society, 2022)
This article describes a concise synthesis of two important fragments (tetrahydropyran [THP] and ketone moieties) of the cytotoxic macrolide (+)-neopeltolide in 10 long linear steps in enantiomerically pure form. Asymmetric Keck allylation to install the required C11 and C13 stereocenters, N-heterocyclic carbene (NHC)-catalyzed oxoacyloxylation to functionalize alkenes, and reductive oxa-Michael addition to construct 2,6-difunctionalized THP unit intramolecularly are the important steps in synthetic efforts. Finally, Keck asymmetric allylation and Lewis acid-catalyzed diastereoselective allylation of the aldehyde were sequentially employed to establish the stereocenters at C11 and C13 positions, respectively.
Keywords: (+)-neopeltolide; Keck allylation; Macrolide; NHC-catalyzed oxoacyloxylation; reductive oxa-Michael addition